Prioritising railway transportation in Malaysia: Aligning with Maqasid al-Shari'ah and United Nations' Sustainable Development Goals. - Che Jamaludin Mahmud, Izmi Izdiharuddin; Md Pauzi, Suria Fadhillah; Amir, Dalila; Mohamad Bahri, Nurwafa Atikah; Binti Rahman, Shamsinar (Journal of Islamic, Social, Economics and Development, 2025)
In Malaysia, the Federal Government invests heavily in railway and road transportation networks that connect cities, a significant financial commitment that has strained the public budget. Given the increasing pressure on public funds, assessing the effectiveness and alignment of these transportation modes with broader societal and global objectives is essential. This article examines the alignment of Malaysia's railway and road transportation systems with Maqasid al-Shari'ah. Maqasid Shari'ah's theory also aligns closely with the United Nations' Sustainable Development Goals. The article argues that railway transportation better supports Maqasid Shari'ah than road transportation, particularly regarding environmental sustainability, public safety, and resource efficiency. In light of these considerations, the article advocates for the Federal Government to prioritise investment in railway infrastructure. Such an approach would promote adherence to Islamic law and contribute to global efforts for sustainable social, economic, and environmental development. This study advances policymaking by providing a comprehensive framework for integrating Maqasid al-Shari'ah into national transportation policy and offering a model for sustainable infrastructure planning.